PatSearch: a program for the detection of patterns and structural motifs in nucleotide sequences - Giorgio Grillo (2003)
Regulation of gene expression at transcriptional and post-transcriptional level involves the interaction between short DNA or RNA tracts and the corresponding trans-acting protein factors. Detection of such cis-acting elements in genome-wide screenings may significantly contribute to genome annotation and comparative analysis as well as to target functional characterization experiments. We present here PatSearch, a flexible and fast pattern matcher able to search for specific combinations of oligonucleotide consensus sequences, secondary structure elements and position-weight matrices. It can also allow for mismatches/mispairings below a user fixed threshold. We report three different applications of the program in the search of complex patterns such as those of the iron responsive element hairpin-loop structure, the p53 responsive element and a promoter module containing CAAT-, TATA- and cap-boxes. PatSearch is available on the web at http://bighost.area.ba.cnr.it/BIG/PatSearch/.